The Use of Lexeme HEAD in English and Indonesian Compound Words: A Contrastive Analysis - Truly Almendo Pasaribu; Danang Satria Nugraha (Makassar State University, 2020)
Compounding is a common word-formation process in Bahasa Indonesia (BI) and English (EN) as it can be found in constructions of the words headline, headmaster, and kepala berita, kepala sekolah in BI, which are widely used by the speakers of the languages. This study scrutinizes the constructions and the senses of lexeme HEAD and KEPALA from contrastive linguistic perspective. It aims at describing (1) The constructions of compound words containing lexeme HEAD and (2) the extended senses of lexeme HEAD in the compound word constructions in BI and EN. The data, taken from Kamus Besar Bahasa Indonesia and Cambridge Online Dictionary, were collected and analyzed using contrastive analysis. The data were collected and analyzed through observation and close reading techniques. The discussion highlighted the similarities and differences of the constructions and extended senses of compound words containing lexeme HEAD. In BI, lexeme kepala is combined with nouns, adjectives, while in English lexeme HEAD is combined with nouns, adjectives, gerunds, and prepositions. In BI the extended senses of lexeme head refer to leader, hair, the most important, the tip of things, and personality, while there are six extended senses in EN, namely leader, hair, the most important part, the tip of things, personality, and movement. The extensions show human creativity to produce and comprehend metaphors and metonymy in context to express ideas that are abstract with something more familiar and concrete